Green jobs, labour market transitions and social protection: Longitudinal analysis for Viet Nam. - Duman, Anil; Ananian, Sévane (International Labour Review, 2026)
This article analyzes labour market transitions toward green employment in Viet Nam and the role of social protection in facilitating these shifts. Using a task-based classification aligned with the International Standard Classification of Occupations (ISCO-08) and longitudinal labour force survey data from 2021–2022, it finds that green jobs constitute about 15 percent of total employment, with younger workers, women, and those with lower education facing greater challenges in accessing green occupations. Social insurance coverage is positively associated with transitions from brown (polluting) or neutral jobs to green jobs among workers with tertiary education, while it has limited or negative effects for those with less education. The study highlights the importance of integrated policies combining social protection and education to promote inclusive and equitable green labour market transitions in developing countries like Viet Nam.